From Hidden Costs to Value: Managing SME-Intermediary Relations in International Markets - Rastrollo-Horrillo, María Ángeles (My University, 2025)
Relationships with international intermediaries and their impact on foreign market performance. Focusing on SMEs that offer differentiated products—where intermediaries are not high-volume actors but require contextual knowledge and close client adaptation— the study highlights the dual role of intermediaries as facilitators and sources of dependency, this study applies the Socio-Economic Approach to Management (SEAM) intervention-research methodology to analyze the tensions that emerge in these relationships and their effects on organizational outcomes. Through a longitudinal case study of a Spanish knowledge-intensive SME, the study identifies key elements of an effective interfirm relationship management model tailored to SMEs, offering actionable insights for improving internationalization strategies. Practical implications highlight the role of consultants in supporting SMEs to harness the benefits of internationalization by addressing hidden dysfunctions and fostering sustainable, collaborative relationships with international intermediaries.
Keywords: Pequeñas y medianas empresas; Mercado monetario; Hidden costs; Socio-economic approaches; SME internationalization; Intermediary relationships; Intervention-research